2016
DOI: 10.3892/or.2016.4639
|View full text |Cite
|
Sign up to set email alerts
|

Forced expression of Nanog with mRNA synthesized in vitro to evaluate the malignancy of HeLa cells through acquiring cancer stem cell phenotypes

Abstract: Abstract. Nanog is a pluripotency-related factor. It was also found to play an important role in tumorigenesis. To date, the mechanisms underlying cervical tumorigenesis still need to be elucidated. In the present study, Nanog mRNA was synthesized in vitro and transfected into HeLa cells. After mRNA transfection, the forced expressed of Nanog in HeLa cells led to markedly increased invasion, migration, resistance to chemotherapeutic agents and dedifferentiation. In a subcutaneous xenograft assay, these cells h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Our cervospheres showed overexpression of these stemness markers compared with their monolayer counterparts, as reported [ 15 , 16 ]. Furthermore, I 2 had the ability to decrease their expression in cervospheres, supporting a role for I 2 in decreasing the tumorigenic capacity of these cancer cells, because as reported in the literature, the decrease of these stem cell markers makes the cancer cells less tumorigenic [ 27 29 , 54 ]. The mechanism proposed by which I 2 decreases cell proliferation is through the interaction and activation of the PPAR gamma receptor [ 34 , 55 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our cervospheres showed overexpression of these stemness markers compared with their monolayer counterparts, as reported [ 15 , 16 ]. Furthermore, I 2 had the ability to decrease their expression in cervospheres, supporting a role for I 2 in decreasing the tumorigenic capacity of these cancer cells, because as reported in the literature, the decrease of these stem cell markers makes the cancer cells less tumorigenic [ 27 29 , 54 ]. The mechanism proposed by which I 2 decreases cell proliferation is through the interaction and activation of the PPAR gamma receptor [ 34 , 55 ].…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, the effect of I 2 on CCSC-like cells was observed by evaluating stemness markers, such as NANOG, SOX2, KLF4 and OCT-4, in cervospheres. It has been demonstrated that there is an increase in expression of these stemness markers in cervical carcinomas, compared with normal cervical tissue, and that their overexpression in cell lines derived from cervical cancer confers them an increased capacity for proliferation, clonogenicity, and tumorigenicity in vitro and in vivo, as well as promoting stem cell characteristics [ 51 54 ]. Interestingly, we observed different stemness marker levels between HeLa and SiHa cervospheres, mainly in KLF4 and SOX2 protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, the tumour spheres derived from both primary tumours and cell lines strongly expressed SOX2, NANOG, and OCT4 (Feng et al 2009). The upregulation of these markers was closely linked to augmentation of self-renewal, tumorigenicity, apoptosis inhibition, cell migration, and chemoresistance in CCSCs (Ding et al 2016;Kim et al 2015). The present study's results show that SF1 may inhibit the CCSCs by selectively suppressing their stemness marker proteins.…”
Section: Suppression Of Ccsc Pluripotent Markers By Sf1supporting
confidence: 56%
“…Therefore, understanding the Nanog-involved mechanism underlying CSC self-renewal and differentiation is essential for developing specific therapy against cancers, especially metastatic cancers. It has been reported that Nanog family members are critical for CSCs: 1) Expression of Nanog proteins is increased in many types of cancer; 2) Enhanced levels of Nanog proteins are related with CSC-like phenotype15,16; 3) Knockdown or knockout of Nanog gene could reduce cancer malignancy17-19. Altogether, Nanog family proteins are pivotal to maintain the function of ESCs under physiological conditions, as well as CSC phenotype under pathological conditions.…”
Section: Introductionmentioning
confidence: 99%